Echocardiographic score to predict neonatal surgery for aortic coarctation in newborns with prenatal suspicion and patent ductus arteriosus. (31st December 2023) - Bartolacelli, Ylenia; Palleri, Daniela; Balducci, Anna; Ragni, Luca; Hasan, Tammam; Bonetti, Simone; Egidy Assenza, Gabriele; Mariucci, Maria Elisabetta; Fabi, Marianna; Angeli, Emanuela; Gargiulo, Gaetano Domenico; Donti, Andrea
Abstract: Introduction: The evaluation of upcoming Aortic Coarctation (CoA) in new-borns with prenatal suspicion entails a close echocardiographic monitor until Arterial Duct (AD) closure, in a department with pediatric cardiological and surgical expertise. The significant number of false-positive prenatal diagnoses causes parental stress and healthcare costs. Aim: The aim of this study was to elaborate an echocardiographic prediction model to be employed at birth when PDA is still present, in patients suspected of CoA during fetal life in order to foretell CoA requiring neonatal surgical intervention. Methods: This retrospective monocentric study included consecutive full-term and late preterm neonates with prenatal suspicion of CoA born from 01 January 2007 to 31 December 2020. Patients were divided into two groups according to the need for aortic surgery (CoA - NoCoA). All patients underwent a comprehensive transthoracic echocardiographic exam in presence of PDA. Multivariable logistic regression was used to create a coarctation probability model (CoMOD) including isthmal (D4), transverse arch (D3) diameters, the distance between a left common carotid artery (LCA) and left subclavian artery (LSA), presence/absence of ventricular septal defect (VSD) and bicuspid aortic valve (BAV). Results: We enrolled 87 neonates (49 male, 56%). 44 patients developed CoA in need of surgical repair. Our index CoMOD showed an AUC = 0.9382, high sensitivity (91%) and specificity (86%) in the prediction of CoA in neonates with prenatal suspicion. We classified neonates with CoMOD > 0 to be at high risk for surgical correction of CoA, with good PPV (86.9%) and NPV (90.9%). Conclusions: CoMOD > 0 is highly suggestive of the need for CoA corrective surgery in newborns with prenatal suspicion.